Immunogenic Properties of MVs Containing Structural Hantaviral Proteins: An Original Study - Layaly Shkair; Ekaterina Evgenevna Garanina; Ekaterina Vladimirovna Martynova; Alena Igorevna Kolesnikova; Svetlana Sergeevna Arkhipova; Angelina Andreevna Titova; Albert Anatolevich Rizvanov; Svetlana Francevna Khaiboullina (MDPI AG, 2022)
Hemorrhagic fever with renal syndrome (HFRS) is an emerging infectious disease that remains a global public health threat. The highest incidence rate is among zoonotic disease cases in Russia. Most cases of HFRS are reported in the Volga region of Russia, which commonly identifies the Puumala virus (PUUV) as a pathogen. HFRS management is especially challenging due to the lack of specific treatments and vaccines. This study aims to develop new approaches for HFRS prevention. Our goal is to test the efficacy of microvesicles (MVs) as PUUV nucleocapsid (N) and glycoproteins (Gn/Gc) delivery vehicles. Our findings show that MVs could deliver the PUUV N and Gn/Gc proteins in vitro. We have also demonstrated that MVs loaded with PUUV proteins could elicit a specific humoral and cellular immune response in vivo. These data suggest that an MV-based vaccine could control HFRS.